Design and optimization of a novel solar cooling system for combined cycle power plants. (10th September 2017) - Calise, Francesco; Libertini, Luigi; Vicidomini, Maria
Abstract: This paper presents the design of a novel Solar Assisted Combined Cycle power plant. The system includes a solar loop equipped with a double stage absorption chiller driven by high-temperature high-vacuum non-concentrating flat-plate solar thermal collectors. The solar loop is coupled to a single-pressure Combined Cycle power plant. The cooling energy produced by the absorption chiller is used to cool gas turbine inlet air, aiming at enhancing system efficiency and electrical capacity. This Solar Assisted Combined Cycle arrangement is analysed through a dynamic system simulation and a thermoeconomic analysis is also performed aiming at determining the optimal set of design and operating parameters. The paper has the objective to prove the technical, energetic and economic feasibility of this technology, especially for hot and dry areas, with respect to other alternative air cooling configurations. In addition, solar collectors operating temperatures are high enough to drive a two stage absorption chiller, showing a Coefficient of Performance roughly two times higher than the one of a conventional single stage absorption chiller. This original configuration was numerically analysed in TRNSYS environment, developing a suitable dynamic simulation model in order to predict system performances. Suitable dynamic models are implemented for all the components included in the system. Special attention is also paid to the design of novel control strategies aiming at maximizing the utilization of solar energy for cooling purposes. In particular, a special control strategy managing cooling water flow is implemented in order to limit as much as possible water condensation within the cooling coil. The simulation also includes a detailed thermoeconomic model which accurately evaluates system capital and operating costs as a function of design and operating parameters. The simulations results show that a very high thermal efficiency of solar collectors, on average equal to 34%, is achieved. Results from the economic point of view were also satisfactory. In fact, the pay back period was about 8 years in the best case. Finally, in order to analyse the effects of the variation of the main design parameters, a parametric analysis is also presented. Such analysis shows that high solar radiation and low ambient humidity are crucial in order to achieve acceptable economic profitability indexes. Highlights: A dynamic simulation of a solar assisted combined cycle power plant is performed. Solar cooling with double effect chiller and flat plate evacuated solar collector. A thorough parametric analysis for a solar assisted CC power plant is presented. A detailed system economic assessment is carried out for different weather zones. High thermal efficiency and reasonable simple pay back are obtained.